Solid fuel processing of Refuse Derived Fuel (RDF) from agricultural waste with latex rubber binder. - Thathong, Vanlop; Pongped, Netnapha; Phimpabut, Nuwut; Ardkaew, Jurairat; Phuangjan, Sakchai; Naksopon, Yutthapong; Tantamsapya, Netnapid (Creative Science, 2024)
There are 5 types of waste materials making up RDF: rubber wood chips (RWC), wood residues (WR), mixed grass (MG), cassava rhizome (CR), leaf fragments (LF). The heating values range 14,693-17,065 kJ/kg. The energy values range 3,509.36-4,075.91 kcal/kg. The moistures range 10.35-16.80 %. The densities range 310-550 kg/m3. Regarding physical and chemical properties of the RDF, Tested with 2 binders: cassava starch sludge and latex rubber with the ratio of 0.50:0.50. The results showed that the moistures range 7.56-8.32 by wt. %. The energy values range 3,474.50-4,245.65 kcal/kg. The densities range 0.45-0.78 g/cm3. The ash contents range 1.06-5.00 by wt.%. The shatter indexes range 0.71-0.93. The ignition times range 5.6-9.8 min. The combustion times range 30-96 min. The combustion rates range 1.38-1.74 g/min. The RDF with 1.0:20.0 water to rubber ratio yields the best efficiency, with 7.68% moisture content and 5.00% ash content. This complies with the local product standard of RDF. It yields 4,226.59 kcal/kg. of heating value. The heavy metal contents from the ash of RDF are within the standard. From the cost and profit analysis, making RDF from cassava rhizome can yield 504.22 baht/rai profit, while selling the rhizome directly yields 199.32 baht/rai profit. GRAPHICAL ABSTRACT HIGHLIGHTS This research result provides new knowledge, which is the use of Latex Rubber as a binder in making RDF. This research result allows rubber farmers to earn more income from selling RDF from rubber tree branches.